Bioactive compounds in Chinese herbal medicine: anti-inflammatory mechanisms targeting neurological disorders - Zhang, Liangxue; Yang, Jiaxin; Yang, Yuhua; Yang, Min; Yang, Juan; Yu, Changyin; Zhang, Haiqing; Tuo, Jinmei; Xu, Zucai (Frontiers in Nutrition, 2025)
Nearly 16% of the world’s population is affected by neurological disorders, including neurodegenerative and neuroimmune diseases caused by acute or chronic inflammation. Inflammatory processes in the central nervous system can exacerbate these diseases by causing neuronal damage and apoptosis. Traditional Chinese medicines have become an important area of research in anti-neuroinflammation and neuroprotection owing to their multi-target effects and favorable safety profiles. In this paper, we review the molecular mechanisms by which bioactive compounds of herbal origin inhibit neuroinflammation and improve disease progression through the modulation of inflammatory factors (including TLR4/MyD88/NF-κB, NLRP3 inflammasomes, and Janus kinase-STAT signaling), epigenetic modifications, cell-type-specific modulation (microglia M1/M2 polarization and astrocyte A1/A2 transformation), and gut-brain axis interactions. These bioactive compounds are mainly classified into those with well-defined chemical structures (such as baicalein, baicalin, berberine, and ginsenoside Rg1), plant extracts (such as tonifying Yang Huiwu Tang, Tongxinluo capsule, Shu Xuning injection, and Xingxiong injection), and preparations based on special mechanisms of action or technical means (such as Hedysari polysaccharides [RHP] and microglial cell exosome carrier berberine and palmatine [Exos-Ber/Pal]). We found that these compounds can improve cognitive and motor dysfunction by inhibiting neuroinflammation while exerting neuronal protection, but their low bioavailability, mechanistic complexity, and lack of clinical translational evidence remain challenges. In the future, a combination of multi-omics techniques, rigorously designed clinical trials, and interdisciplinary strategies will be required to promote the precise application of herbal medicines in neuroinflammation-related diseases.